2014
DOI: 10.1111/jep.12191
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes on and experiences with evidence‐based medicine: a qualitative study

Abstract: According to the results of this study, providing suitable conditions and appropriate planning to address identified barriers and encouraging students can promote EBM practice. Also, more extensive EBM integration in medical curricula and clinical settings by leading faculty members would prompt medical students to use EBM in their daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
0
16
0
2
Order By: Relevance
“…All studies mentioned show the orientation of physicians about the importance of learning and teaching EBM for practice. It seems that the implementation of EBM in medical curricula would be welcomed, as concluded in recent literature 30 31…”
Section: Discussionmentioning
confidence: 87%
“…All studies mentioned show the orientation of physicians about the importance of learning and teaching EBM for practice. It seems that the implementation of EBM in medical curricula would be welcomed, as concluded in recent literature 30 31…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have addressed teaching EBM skills and knowledge to medical students and health professionals, and changing attitudes towards EBM in both developed and developing countries [10, 11]. In light of recent lack of safety, and lack of both human and material resources in the Middle East and North Africa region, more flexible and affordable means are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to EBM awareness in developing countries are several; in Iran, a systematic review was conducted to investigate obstacles to EBM, to find the most important factors which were; the absence of proper facilities, positive attitudes and adequate training [10]. In Syria, Alahdab et al explored the barriers to EBM awareness in 2012, and reported that the most important barriers were; the absence of EBM curricula, equipment and facilities, in addition to difficulties in accessing information, institutional subscriptions to medical journals, and sufficient IT hardware [11].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that we could obtain more accurate results by reviewing the comments of other students. Finally, regarding the potentiality of qualitative studies, [18][19][20] we recommend that other qualitative studies with the same topic be performed to provide a strengthened foundation for TSOs. This study was designed regarding the condition of 4th and 5th Olympiads.…”
Section: Resultsmentioning
confidence: 99%